Southwest Research–Extension Center, Field Day 2006 (Kansas Agricultural Experiment Station Research Reports, 2006)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2006; SRP961; crops; tillage; irrigation; weeds science; insect control